Good Governance Implementation in the Development of Sustainable Tourism; The Portrait of Padang City Government - Siskawati, Eka; Yentifa, Armel; Zahara; Dela Gusta, Haniva (Jurusan Akuntansi Politeknik Negeri Padang, 2020)
This article describes on how the implementation of good governance is carried out by Padang City Government in sustainable tourism management. This research is aimed to (1) Overseeing the good governance implementation in Padang City Government in term of the development of sustainable tourism destinations. (2) Analyzing the sustainable tourism management viewing it from agency theory. It is a qualitative descriptive research, and performed in Padang City Culture and Tourism Office. More over, data collection utilizes observation, interview, and documentation. The good governance principle employed in this research are accountability, participation, and transparency. The result shows that the implementation of good governance at Padang City Culture and Tourism Office has been achieved well. It is as a result of the agency relationships occured within local government; the relationship with the executive in the role of Culture and Tourism Office, and with public as the community.